Rechtliche Rahmenbedingungen von Open Access-Publikationen - Spindler, Gerald (Universitätsverlag Göttingen, 2006)
Even earlier than other sectors of society, science was confronted with the Internet as a new communication medium. Yet it has lasted several years until the Internet has gained reputation as a publication medium for scientists. This development is accompanied by an increasing concentration on the side of scientific publishers, which has lead for some disciplines to almost monopolistic situations. Conversely, the financial resources to purchase and provide access to scientific publications are shrinking on the side of the customers - libraries and researchers, but also other sectors of the public. This results in a disastrous spiral, known as the so-called "publication crisis." As one solution to this crisis new publication concepts using the internet have emerged. They are characterized by the fact that they provide access to scientific works largely free and unrestricted - Open Access. This book "Legal Framework for Open Access" is designed as a practical guide and aims to help authors who want to publish Open Access. The content includes: Introduction to Open Access • Facts on Copyrights • Open Access in Universities • Open Access Licenses • Technical protection measures and Open Access • Retrodigitalisation issues • Liability of institutional repositories for archived Open Access publications • Implications regarding competition law • Public legal and organizational framework for Open Access